MANAJEMEN STRATEGI KEUNGGULAN BERSAING PERUSAHAAN - Dina Sarah Syahreza; Dimas Rifai; M Rizky Fernanda; Aisyah Fatma Neliza; Rifka Anisa; Mega Sagak Rotua Lumban Tobing (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to see how strategic management in the competitive advantage of a company. The method used is a qualitative-literature study approach, where data is collected from various sources such as books, journals, and pre-existing research. The results of this study show that success in implementing competitive advantage strategy management depends on the company's ability to select and focus on key elements such as innovation, cost efficiency, product or service quality, customer service, and adaptation to market changes. The importance of continuous performance monitoring and rapid response to market dynamics cannot be ignored. Companies that are able to adapt to change can maintain their competitive advantage. Employee engagement, leader commitment, and building a strong brand image are also decisive factors in creating a successful business environment. In the era of globalization and increasingly fierce competition, companies need to build and maintain their competitive advantage to stay relevant and win the hearts of customers.